The Capstone Experience for the Religious Studies Major - Upson-Saia, Kristi (Teaching theology and religion, 2013)
The purpose of this essay is to offer a survey of religious studies capstones from twenty-nine U.S. colleges and universities, to identify the most common frustrations about the capstone, and to observe how departments resolve such frustrations. I conclude that the most successful capstones – in terms of students' performance and faculty satisfaction – are those that are carefully linked to their department's major curriculum, pedagogies, and staffing, that set out to achieve a reasonable set of objectives, and that are aligned with their institutional mission, culture, and expectations for assessment. Yet, I argue that it is becoming increasingly difficult to design our capstone experiences according to the above principles because of the proliferation of departmental and institutional pressures we presently face. Finally, I offer some guidelines by which we might devise or revise our capstones to alleviate some of the most common pressures.